The Association between the PR Interval and Left Ventricular Measurements in the Multiethnic Study of Atherosclerosis - Michael P. Husby; Elsayed Z. Soliman; Jeffrey J. Goldberger; Kiang Liu; Don Lloyd-Jones; Ramon Durazo-Arvizu; Holly Kramer (Cardiology Research and Practice)
Introduction. Few studies have examined the association between the PR interval (PRi) and subclinical cardiovascular disease measures. Methods and Results. The Multiethnic Study of Atherosclerosis (MESA) is a population-based study of 6814 men and women aged 45–84 years without clinical cardiovascular disease and 4962 had complete baseline data on cardiac magnetic resonance imaging measures of LV dimension and ejection fraction and surface electrocardiogram. Linear regression models were constructed to determine the adjusted association between the PRi and measures of LV stroke volume, LV mass, LV end-systolic and end-diastolic volumes, and ejection fraction. Overall, mean age was 61.5 years, and 47.6% were male and race/ethnicity was white in 39.1%, Chinese in 13.1%, African-American in 25.7%, and Hispanic in 22.2%. The PRi ranged from 88 to 308 ms with a median value of 162 ms. As a continuous variable, every standard deviation unit (25 ms) increment in PRi was associated with a 2.00 mL (95% CI 1.52, 2.48) higher stroke volume, a 3.08 g (95% CI 2.30, 3.86) higher LV mass, a 1.36 g/m2 (95% CI 0.96, 1.76) higher LV mass index, and 1.31 mL (95% CI 0.88, 1.73) higher end-systolic and 3.31 mL (95% CI 2.58, 4.03) higher end-diastolic volumes after adjustment for all covariates. No significant association was noted between the PRi and LV ejection fraction. Conclusions. A prolonged PRi is associated with LV measures and may in part explain the link between a prolonged PRi and cardiovascular outcomes.